ANALISIS PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP INSTITUTIONAL OWNERSHIP - Konny Hanggarwati; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
This study examined the influence of CSR disclosure to Institutional ownership. Institutional ownership is the ownership owned by institution or agencies. CSR disclosure in this study consists of four dimensions, namely the dimensions of employees relation, community involvement, products and environments.This study used the multiple linear regression analysis. The multiple linear regression analysis used to examined the effect of CSRD dimensions of employee relation, community involvement, product and environment on the Institutional Ownership. The sample is annual report high-profile companies listed on the Indonesia Stock Exchange in 2010-2011.The result in this study indicate that overall of CSR disclosure has a positive and significant impact to the Institutional Ownership. CSR disclosure dimensions of employee relation also has a positif and significant impact to the Institutional Ownership. However, CSR disclosure dimensions of community involvement, product and environment have a positif impact but not significant.